132 Treatment of neuromyelitis optica with azathioprine. Issue 3 (9th February 2012) - Elsone, L; Leite, M I; Brown, R; McNeillis, B; Palace, J; Boggild,; Jacob, M A
Abstract : Introduction: Neuromyelitis optica (NMO) is an inflammatory demyelinating condition, usually causing relapsing optic neuritis and longitudinally extensive transverse myelitis. Patients with limited forms are said to have NMO spectrum disorder (NMOSD). Azathioprine (AZA) is the most commonly used immunosuppressive drug to prevent relapses. However, its effectiveness over prolonged follow-up in larger cohorts is unknown. Aim: Aim of this study was to analyse the effectiveness and tolerability of AZA in Aquaporin4 antibody positive NMO/NMOSD patients. Methods: We retrospectively reviewed 54 Aquaporin-4 antibody positive NMO/NMOSD patients treated with AZA from two tertiary neurological centres in the UK. Results: AZA was the first steroid-sparing drug to be used in 80% patients, 60% of whom were also on prednisolone. Median annualised relapse rates (ARR) pre treatment was 1.59 (0–26). At a median of 2 (1–10) years after starting treatment the median ARR was reduced to 0 (0–4.8), p<0001. AZA was discontinued in 21 (39%) patients: nine due to side effects, five due to lack of response and seven due to death. Conclusion: AZA in combination with prednisolone is an effective, cheap and convenient first line drug in NMO. However morbidity and mortality in NMO is high and controlled trials to compare it with other treatments (mycophenolate, mitoxantrone and Rituximab) are needed.